Semar AquaConnect: A Closed-Loop IoT System for Real-Time Monitoring and Autonomous Control in Catfish (Pangasianodon hypophthalmus) Larvae Rearing - Rafif Zainun Ridhwan; Basino; ⁠Berbudi Wibowo; Rahmad Surya Hadi Saputra; ⁠I Ketut Daging; Yusuf Syam; Akhmad Syarifudin; Ade Hermawan (Journal of Embedded Systems, Security and Intelligent Systems, 2026)
Purpose – This study aims to develop and validate Semar AquaConnect, a closed-loop Internet of Things (IoT) system for real-time monitoring and automated environmental control in catfish (Pangasianodon hypophthalmus) larval rearing tanks. Design/methods/approach – The system integrates an ESP32-based controller with sensors for temperature, pH, dissolved oxygen, total dissolved solids, and water level, as well as relay-based control of pumps, an aerator, and an immersion heater. A web-based dashboard and Telegram Bot were also developed for remote monitoring, data visualization, and emergency notifications. System performance was evaluated through sensor accuracy testing and repeated simulated extreme-condition scenarios (n=5). Findings – The results showed low mean differences of 0.12°C for temperature, 0.33 for pH, 0.08 mg/L for dissolved oxygen, and 5.10 ppm for total dissolved solids. In simulated scenarios, the system achieved a 100% relay activation success rate, including responses to critical pH fluctuations and temperature drops. Mean response latency ranged from 0.85 ± 0.10 s to 1.42 ± 0.18 s. Research implications/limitations – This study is limited to technical validation and has not yet included live biological trials to measure actual larval survival improvement. Originality/value – The study presents an integrated smart aquaculture platform combining multi-parameter sensing, autonomous actuator control, and dual-interface remote monitoring for catfish larval rearing.